Effect of waste-based micro cellulose fiber as pore maker on characteristics of fired clay bricks - Arslan, Çağrıalp; Gençel, Osman; Borazan, Ismail; Sutcu, Mucahit; Erdoğmuş, Ertuğrul; Gençel, Osman; Erdoğmuş, Ertuğrul; Arslan, Çağrıalp (Elsevier Sci Ltd, 2021)
This study was performed to the evaluation of waste micro cellulosic fiber (CF) as a pore-making material in fired clay brick. The waste CF at the loading ratio of 2.5 - 15 wt% was used in the clay bricks. Cylindrical-shaped samples were prepared and the firing process was performed at 950 degrees C for two hours. The characterization of the bricks was done by the bulk density, apparent porosity, water absorption, compressive strength, thermal conductivity, loss on ignition, and efflorescence analysis. The fractured bricks after the compressive strength test were analyzed via the SEM, EDS, and XRD analysis. The test results revealed that porosity, water absorption, and loss on ignition of clay brick increase as its bulk density, compressive strength, and thermal conductivity decrease with the addition of waste CF. When the waste CF was inserted into the clay brick body, a considerable increment was observed in thermal performance with 0.267 W/mK with respect to control brick (0.893 W/mK) whereas the mechanical performance sharply decreases from 25.4 to 1.4 MPa. Although the introduction of waste CF to the brick body deteriorate the compressive strength due to micropores caused by CF, a better result was achieved with fiber addition of 2.5 wt% among the bricks. However, the decrease in thermal conductivity value of the clay brick was about 70% when the added amount of waste CF reached 15 wt%. The brick containing 2.5 wt% CF presents the optimum results among the bricks and can be evaluated as a semi-structural brick when the bulk density (1.98 g/cm3), compressive strength (14.0 MPa), and thermal conductivity (0.574 W/mK) results are considered. In addition, also the brick containing 5 wt% CF can be used in non-load-bearing applications regarding the results of related properties. The fired clay bricks present a slight level of efflorescence. Considering the findings obtained from the present study, the waste CF can be used as a pore maker in the production of fired clay bricks and the bricks can be evaluated in interior structural applications.
Keywords: Fired Clay Brick; Recycling; Micro Cellulose Fiber; Pore Making Material; Thermal Conductivity; Energy Saving